Hungary: Social Challenges of an Aging Society - Tóth, Hilda; Mélypataki, Gábor (Sustainability Of The Social Security System: Demographic Challenges and Answers in Central Europe, 2023)
One of the main challenges facing the Hungarian social security system is demographic change. The steadily shrinking labour force in a pre-ageing society will soon pose a problem for finance. In the current payments model, contributions should cover the entire expenditure side, which already works only with corrections. And changes in the structure of society will raise a host of issues for which the present legislator is not prepared. This study highlights these important issues such that, together, we can find good practices to prevent the demographic changes that are a harbinger of the future.KEYWORDS: social rights, Constitutional Court, pension system, healthcare system, social security benefits, solidarity, green health, sustainability